BLENDED LEARNING AS A MODEL OF DIGITAL EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
Blended learning has emerged as an effective model of digital education that integrates traditional face-to-face instruction with online learning environments. This article examines the theoretical foundations, advantages, and challenges of blended learning, as well as its role in modern educational systems. The study highlights that blended learning enhances flexibility, promotes student-centered approaches, and improves learning outcomes. At the same time, it identifies key challenges such as technological barriers, lack of teacher training, and assessment difficulties. The findings suggest that, despite existing limitations, blended learning represents a sustainable and innovative direction for the future of education.